On Autonomy of Aesthetic Education - Sasnauskienė, Jadvyga (Problemos, 1983)
Different views on the aim and tasks of aesthetic education are considered. Basing on an analysis of man’s aesthetic attitude to reality and his part in the process of personality formation a conclusion is drawn that the above attitude is a relatively independent form of valuable attitude, having its own specific character. Thus, aesthetic education is a relatively independent component of the general educational process.